Pengaruh Sikap Kerja Kecerdasan Emosional Dan Etos Kerja Terhadap Kinerja Pegawai Sekretariat DPRD Kabupaten Padang Lawas - Eddi Mirson; Ardiansyah Putra; Evi Novita; Handy Karosse Lini Pohan (Jurnal Prodi Fakultas Ekonomi-UISU, 2022)
This formula research internal issue is how influence work attitude on employees performance. How influence of emotional intellegence on employees performance. How influence of work ethic on employees performance. How influence of work attitude, emotional intellegence, and work ethic on employees performance. This research target is to for know influence and analyze of work attitude on employees performance. For know influence and analyze of emotional intellegence on employees performance. For know influence and analyze work ethic on employees performance. For know influence and analyze work attitude, emotional intellegence and work ethic on employees performance. Sample in this research amount to 30 employees. Technique analyze data which used in this research is analysis of regresi multiple linear. This research result explain of work attitude effect positive and significant on employees performance. Emotional intellegence effect positive and significant on employees performance. Work ethic effect positive and do not significant on employees performance. Work attitude, emotional intellegence, and work ethic effect and positive and significant on employees performance